Mentoring of Beginning Business Education Lecturers for Sustainable Pedagogical Skills Development in State Universities in Rivers State (Global Journal of Management and Business Research, 2020)
This study explored the mentoring needs of beginning business education lecturers as a way of achieving sustainable pedagogical skill development in state universities in Rivers State. Two research questions and two hypotheses were formulated to guide the study. A survey research design was adopted for the study and the entire population of lecturers in the two state universities in Rivers State were used. Questionnaires were distributed by the researchers and then retrieved for analysis on completion. Mean and standard deviation were used to answer the two research questions while z-test statistics was used to test the two hypotheses. The findings of the study revealed that mentorship in academic publications, in students' assessment, and in research writing among others are the practices needed for mentoring of beginning Business Education Lecturers.
Keywords: mentoring; business education; pedagogical skills development